Case Report: Severe Complement-Mediated Thrombotic Microangiopathy in IgG4-Related Disease Secondary to Anti-Factor H IgG4 Autoantibodies - Breville, Gautier; Zamberg, Ido; Sadallah, Salima; Stephan, Caroline; Ponte, Belen; Seebach, Jörg D. (Frontiers in Immunology, 2021)
Objective To first describe and estimate the potential pathogenic role of Ig4 autoantibodies in complement-mediated thrombotic microangiopathy (TMA) in a patient with IgG4-related disease (IgG4-RD). Methods This study is a case report presenting a retrospective review of the patient’s medical chart. Plasma complement C3 and C4 levels, immunoglobulin isotypes and subclasses were determined by nephelometry, the complement pathways’ activity (CH50, AP50, MBL) using WIESLAB® Complement System assays. Human complement factor H levels, anti-complement factor H auto-antibodies were analyzed by ELISA, using HRP-labeled secondary antibodies specific for human IgG, IgG4, and IgA, respectively. Genetic analyses were performed by exome sequencing of 14 gens implicated in complement disorders, as well as multiplex ligation-dependent probe amplification looking specifically for CFH, CFHR1-2-3, and 5. Results Our brief report presents the first case of IgG4-RD with complement-mediated TMA originating from both pathogenic CFHR 1 and CFHR 4 genes deletions, and inhibitory anti-complement factor H autoantibodies of the IgG4 subclass. Remission was achieved with plasmaphereses, corticosteroids, and cyclophosphamide. Following remission, the patient was diagnosed with lymphocytic meningitis and SARS-CoV-2 pneumonia with an uneventful recovery. Conclusion IgG4-RD can be associated with pathogenic IgG4 autoantibodies. Genetic predisposition such as CFHR1 and CFHR4 gene deletions enhance the susceptibility to the formation of inhibitory anti-Factor H IgG4 antibodies.